WORKSHOP PENGGUNAAN SARI DAUN PACAR KUKU (Lawsonia inermis L) SEBAGAI PENGGANTI SAFRANIN PADA PEWARNAAN GRAM - Siregar, Sa’adah; Rizky, Vincentia Ade; Krisdianilo, Visensius; Jayanti, Neti Eka; Sitanggang, Morischa Deyla (LPPM Institut Pendidikan Nusantara Global, 2023)
Gram staining is one way to differentiate gram-positive bacteria and gram negative bacteria. Gram staining in the laboratory is done with using a solution of gentien violet, iodine, alcohol, and safranin. Leaf henna nail (Lawsonia inermis L) is a plant that produces the reddish yellow molecule is called Lawsone. Additionally leaves henna nails It also contains anthocyanins which produce a reddish orange color. This Community Service aims to inform the audience about the benefits of henna leaf extract (Lawsonia inermis L) is effectively used as a substitute for safranin in gram staining. The results of the workshop show that the audience can understand the benefits of henna nail leaf extract as a substitute for safranin in gram staining, but this is only an alternative.